Observations on some causes of sudden cardiac death - Niazi, Mustafa (The University of Edinburgh, 1949)
I. General Statement: The review of my own 3,250 case -records of necropsies for the Medico -Legal Department of the Ministry of Justice of Egypt over a period of nine years has revealed the following data:-

(a) Death from natural causes occurred in 1,980 cases; 60.9%. (b) Sudden death occurred in 760 cases; 38.4% of those dying from natural causes. (c) Sudden cardiac death occurred in 365 cases; 48% of the cases of sudden death.

The records of sudden cardiac death (365 cases) were extracted for study.

These cases were classified and grouped on a pathological basis.

The study of these cases was undertaken from consideration of the following points:-

1. Incidence of the disease in post mortem series. 2. Age incidence. 3. Sex incidence. 4. Race. 5. Bodily constitution. 6. Past history. 7. Social conditions. 8. Associated diseases. 9. Predisposing factors. 10. Symptoms prior to death, and their duration. 11. Duration of life after the onset of the disease.

II. The main groups of diseases resulting in sudden cardiac death in this series were as follows:-

(a) Coronary artery disease and its sequelae $3.14 (b) Infectious process directly affect- ing the myocardium 7.6> (c) Syphilitic affection of the aorta, aortic valve, and coronary arteries 4.6;0 (d) Rheumatic fever affecting the heart and aortic valve 3.0% (e) Adiposity of the heart 1.7%

III. Incidence of sudden cardiac death pre- dominated in males over females in a ratio of 2.7 : 1.

IV. A summary will now be presented of the causes of sudden cardiac death in this post mortem series on a basis of pathological anatomy.